Perancangan media promosi dengan pendekatan storytelling untuk pengenalan kopi babah kacamata Salatiga - Kristina Budi; Michael Bezaleel; Jasson Prestiliano (IT Explore: Jurnal Penerapan Teknologi Informasi dan Komunikasi, 2026)
Consumption of sweetened coffee with various mixtures has become an unhealthy habit for the younger generation. Kopi Babah Kacamata, a legendary tubruk coffee in Salatiga, has been affected by this change. Many people are still unaware of the brand and the consumption of black coffee is declining. Therefore, this research will discuss the positive impact of consuming tubruk coffee with the Kopi Babah Kacamata brand as a soft selling medium for young people. This research uses mixed-sequel exploratory method and linear strategy in its design. The results of this study can be concluded that promotional videos with a storytelling approach for Kopi Babah Kacamata effectively introduce to the target audience.